2016
DOI: 10.1039/c6cc06887a
|View full text |Cite
|
Sign up to set email alerts
|

Explosive enantiospecific decomposition of aspartic acid on Cu surfaces

Abstract: Aspartic acid adsorbed on Cu surfaces is doubly deprotonated. On chiral Cu(643) its enantiomers undergo enantiospecific decomposition via an autocatalytic explosion. Once initiated, the decomposition mechanism proceeds via sequential cleavage of the C3-C4 and C1-C2 bonds each yielding CO, followed by conversion of the remaining species into N[triple bond, length as m-dash]CCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(95 citation statements)
references
References 36 publications
6
88
1
Order By: Relevance
“…Differently from studies from Gellman's group, 24,25 we hypothesize that the NH 2 amine group is not interacting with the surface. In fact, since no contribution from the NH 2 group is visible in corresponding infrared data, we deduce that, at low coverage, its plane is parallel, or almost parallel, to the surface.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Differently from studies from Gellman's group, 24,25 we hypothesize that the NH 2 amine group is not interacting with the surface. In fact, since no contribution from the NH 2 group is visible in corresponding infrared data, we deduce that, at low coverage, its plane is parallel, or almost parallel, to the surface.…”
Section: Resultscontrasting
confidence: 78%
“…More recently, Gellman and co-workers have studied ASP films evaporated (in racemic mixture or as pure D or L enantiomers) in UHV conditions, to characterize the enantiomer nature of ASP molecules on chiral and achiral copper surfaces. 21,22,23,24,25 All these studies have in common the conclusion that ASP chemical form after adsorption on a surface depends on the film coverage. However, this form is different according to the substrate.…”
Section: Asp C 4 H 7 No 4 (mentioning
confidence: 99%
“…Aspartic acid adsorption on Cu(100), Cu(110) and Cu(111) revealed that on all three surfaces, Asp was adsorbed as a zwitterion ( -O2CCH(NH3 + )CH2CO2H) in the multilayer but as a doubly deprotonated anion ( -O2CCH(NH2)CH2CO2 -) in the monolayer. 29,42 Furthermore, Cu(111) is relevant as it is the structure of the terrace on the chiral Cu(643) R&S surfaces.…”
Section: Xps Of D-pro/cu(111)mentioning
confidence: 99%
“…The N 1s spectra (Figure 2, center panel) reveal a peak at 402.0 eV (blue dashed curve) in the multilayer that is assigned to the >NH2 + group 29 and is absent in the monolayer spectrum. Conversely, there is a peak at 399.5 eV in the monolayer spectrum (red curve) assigned to the >NH group 29 that is present but much less intense in the multilayer spectrum. This indicates that in the D-Pro multilayer, the imine group is protonated while in the monolayer, it is not.…”
Section: Xps Of D-pro/cu(111)mentioning
confidence: 99%
See 1 more Smart Citation